Kepadatan Leksikal Paragraf Skripsi Berbahasa Inggris: Analisis Unsur Qualifier - Mubasyir, A. Djawad (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2014)
This study compared the lexical density of undergraduate theses in the English Department of Universitas Negeri Jakarta with that of the articles published in certain reputable international journals. The approach used was Systemic Functional Linguistics (SFL). The result of the comparison shows that the paragraphs in the undergraduate theses have a lower average lexical density than those in the journal articles.